EFFECTS OF BIOPESTICIDES IN Tetragonisca angustula LATREILLE (HYMENOPTERA: MELIPONINAE) POLLINATORS - Prescinato de Oliveira, Carlos Vinício; Sinópolis Gigliolli, Adriana Aparecida; Galhardo, Douglas; Moreira, Daiani Rodrigues; Ronqui, Ludmilla; Santos, Simone Aparecida; Arnault Toledo, Vagner Alencar; Ruvolo-Takasusuki, Maria Claudia Colla (Arquivos de Ciências Veterinárias e Zoologia da UNIPAR, 2020)
Stingless bees Tetragonisca angustula (Latreille) (Hymenoptera: Meliponinae) are pollinators of native and cultivated plants, are therefore in contact with areas contaminated by pesticides. These native bees were evaluated for changes in gene expression of esterase isoenzymes and peptides after contamination by contact with insecticides growth regulators Gallaxy ® EC 100, Natuneem and Azamax after 48, 120, 168 hours, 30 and 60 days. EST-4 presented an increase in relative activity after contamination with Gallaxy ® 100 EC at 6.2 × 10-2 g a.i/mL, Natuneem at 7.5 × 10-5 g a.i/mL and Azamax at 1.2 × 10-3 g a.i/mL after 60 days, 48 h and 60 days, respectively. Inhibition of the relative activity of EST-4 was detected after contamination by the Natuneem at 1.5 × 10-5 g a.i/mLand Azamax at 1.2 × 10-3 g a.i/mL after 48 h and 30 days respectively. The insecticides growth regulators promoted changes in protein synthesis of adult workers of T. angustula resulting in an increase or decrease in the relative intensity of bands, and the appearance of new peptides compared with controls. Changes in protein synthesis have been identified mainly after long period of contamination, 120 and 168 h with the IGRs Gallaxy ® EC 100 (at 0.78 and 1.25 g a.i/mL), Azamax (at 1.2 × 10-3 and 6 × 10-3 g a.i/mL) and Natuneem (at 7.5 × 10-5 and 3 × 10-3 g a.i/mL) and 60 days with Natuneem (at 1.5 × 10-5 g a.i/mL).